Penerapan Teknologi Augmented Reality Sebagai Alternatif Media Promosi Pariwisata Kabupaten Banyumas - Ferdinanda; Anggar Ranawijaya; Emi Iryanti (Ikatan Ahli Informatika Indonesia (IAII), 2020)
Augmented Reality (AR) is known as an interactive technology that is able to project virtual objects into real objects in real time. Banyumas is an example of a district that has a lot of tourism commodities because of its diverse culture and its lack of promotion. This promotional media was created using AR with marked based tracking method. This method utilizes the function of the marker as the media that acts to display the virtual object, the marker will be recognized by the application through the camera device regarding the position and orientation of the object. For the process of making this application using Unity as a tool and Vuforia as a database for markers. The testing phase using the ISO 25010 standard is an evaluation of the quality of the software system specifically based on product quality consisting of eight characteristics, namely functional suitability, performance efficiency, compatibility, usability, reliability, security, maintainability, and portability. This study uses three tests of eight characteristics, namely function suitability, compatibility and usability. The results of this application quality analysis obtained functional suitability test results of 97.5% and compatibility results obtained results of 100% for usability with a percentage of 88.6%.